Evaluation of the applicability of SDMA for early diagnosis of CKD in felines and survey of staging and tests used in routine practice - Costa, Rafaela Cristina Cardoso; Pereira, Jaqueline Aparecida Sousa; Alexandrowitsch, Fátima Christina França; Filho, Marcelo de Figueiredo Filardi; Lemes, Bruna Cardoso; Cunha, Rafaela de Oliveira; Ferreira, Thassiane Luciana; de Carvalho, Nara Ladeira; Guedes, Elizângela (Seven Editora, 2024)
Felines, due to anatomical, physiological and dietary aspects, have a certain predisposition to problems affecting the renal system, highlighting chronic kidney disease (CKD). This disease is a progressive and irreversible disease, being an important cause of death in felines, especially with advanced age. Unfortunately, due to its initial signs being silent, it ends up resulting in late diagnoses, resulting in the appearance of clinical manifestations only during the worsening of the condition. Thus, the symmetric dimethylarginine biomarker (SDMA) has been raised as an alternative for assessing the existence of CKD early when compared to the quantification of serum creatinine, and in 2015 it was incorporated as a method for staging according to the International Society of Renal Interest (IRIS), representing a complementary test and aid in the classification of the stages of this disease, especially in the substages. Thus, the reason for this research was to disseminate a questionnaire to verify the applicability of this biomarker in the routine of veterinarians, in addition to addressing other important issues within this theme. DOI:https://doi.org/10.56238/sevened2024.025-033